Adaptation in ethnobotanical knowledge of Prunus cerasoides among different ethnic groups, religions and culture in Nepal - Dipak Khadka; Ripu M. Kunwar; Rainer W. Bussmann; Sijar Bhatta; Sanu R. Maharjan; Dafang Cui; Shi Shi (Trees, Forests and People, 2025)
Societies, ecosystems and species, including medicinal plants worldwide, are increasingly impacted by the changing context of ecology, land use, socio-economy and climate. All these groups have been adapting to these adversaries. However, conventional adaptation strategies to these changes may not always be effective at helping people or ecosystems to reduce their vulnerabilities. We conducted this study to understand and bolster the ethnobotanical adaptation knowledge regarding using Prunus cerasoides in the trajectory of socio-cultural changes in Nepal. We surveyed 713 participants from eastern, central, and western Nepal to collect primary data. We calculated the species use fidelity level (%) to understand the commonly used plant reports. The Jaccard similarity index was used to investigate the cross-cultural use of P. cerasoides among different sample groups. The Kruskal Wallis test was employed to test the difference in knowledge levels within religion and ethnicity. Out of recorded 11 different use categories of P. cerasoides, eight categories had significant fidelity levels, which include cooking/heating (87.94 %), house construction (86.40 %), livestock feed (84.57 %), culture (79.38 %), food (44.32 %), medicine (26.37 %), apiculture (22.72 %), and agriculture (5.05 %). The species’ uses shared by various religious and ethnic groups differed significantly. In the religious group, Hindus used the species more consistently (median=5 and interquartile range (IQR)=1); likewise, among the ethnicities, Chettri and Thakuri used species more consistently than other ethnic groups (median = 5 and interquartile range (IQR)=1). Among the religious groups, there is a significant difference in fidelity level of culture, livestock feed, food, cooking /heating energy, apiculture, and others. However, in changing contexts, P. cerasoides faces increasing conservation challenges as socioeconomic transformations, deculturation and abandonment of agricultural lands and traditional practices have become prevalent in recent decades.